PENGARUH MODEL COURSE REVIEW HORAY DAN GAYA BELAJAR TERHADAP HASIL BELAJAR SISWA SD NEGERI 02 WANAREJAN - Damayanti, Maya (Jurnal Kualita Pendidikan, 2023)
A teacher in carrying out teaching assignments is really required to first know and master learning models in order to change learning situations for the better and obtain optimal learning results, especially in subjects. One that is considered capable of adapting learning styles to the learning outcomes of Indonesian subjects that make it easier for students is learning with the course review horay model. Choosing the right learning model is one of the solutions so that students can easily understand and enjoy the material presented. Apart from that, knowing the learning styles (way of learning) of different students makes a formula for teachers to explore the character of learning for each student. The purpose of this study was to determine the effect of the Course Review Horay model and learning styles on Indonesian language learning outcomes for students at SDN 02 Wanarejan. This research is a quantitative research type of experimental research with Quasy Experimental Design. The independent variable of this study is the Course Review Horay learning model and learning style while the dependent variable is student learning outcomes. Data analysis techniques used are validity and reliability tests and to answer the research objectives using multiple linear regression analysis. The results of the study are based on the average score obtained compared to the rating scale, where a score of 60 <n ? 100 is included in the very good category, so the instrument as a whole has very good content validity, and can be used with a little revision. based on the V value obtained from items 1-20 which ranged from 0.78 to 0.100, all items from the instrument were considered to have sufficient content validity.